ANALISIS REALISASI PENDAPATAN BUKAN PAJAK LAINNYA PADA KEMENTERIAN DESA, PEMBANGUNAN DAERAH TERTINGGAL, DAN TRANSMIGRASI - dinar, lathifah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to analyze the realization of other non-tax revenues managed by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. Non-tax revenue, known as Non-Tax State Revenue (PNBP), plays a crucial role in financing development at the village level. In this study, a descriptive qualitative approach was used with a focus on analyzing the Ministry's financial statements (LRA) for fiscal year 2023, in order to provide a clear picture of the management of these revenues. The results showed that the realization of non-tax revenue reached Rp13,910,971,728.00, which exceeded the set target by a percentage reaching 630.17%. This study shows that most of the revenue came from the TAYL Goods Expenditure Reception, which was a return on the findings of the Supreme Audit Agency (BPK) in the previous year. This highlights the importance of non-tax revenue management and its impact on the budget as well as sustainable village development, while also showing great potential in increasing the contribution of state revenue through more effective and transparent management.